The twelfth Imam - Rosenberg, Joel C.,1967- (Carol Stream, Ill. : Tyndale House Publishers, 2010)
With the prophecy of the Twelfth Imam seemingly fulfilled, Iran's military prepares to strike Israel and bring about the End of Days. CIA operative David Shirazi must take action to save his country and the world, but the clock is ticking
Keywords: Intelligence officers -- Fiction -- United States; Nuclear warfare -- Fiction -- Prevention; Prophecy -- Fiction -- Islam; Fiction; Fiction; Suspense fiction; Christian fiction